Quantitative and spatio‐temporal features of protein aggregation in Escherichia coli and consequences on protein quality control and cellular ageing - Winkler, Juliane; Seyberth, Anja; König, Lars; Pruggnaller, Sabine; Haselmann, Uta; Sourjik, Victor; Weiss, Matthias; Frangakis, Achilleas S.; Mogk, Axel; Bukau, Bernd (The EMBO journal, 2010)
The aggregation of proteins as a result of intrinsic or environmental stress may be cytoprotective, but is also linked to pathophysiological states and cellular ageing. We analysed the principles of aggregate formation and the cellular strategies to cope with aggregates in Escherichia coli using fluorescence microscopy of thermolabile reporters, EM tomography and mathematical modelling. Misfolded proteins deposited at the cell poles lead to selective re‐localization of the DnaK/DnaJ/ClpB disaggregating chaperones, but not of GroEL and Lon to these sites. Polar aggregation of cytosolic proteins is mainly driven by nucleoid occlusion and not by an active targeting mechanism. Accordingly, cytosolic aggregation can be efficiently re‐targeted to alternative sites such as the inner membrane in the presence of site‐specific aggregation seeds. Polar positioning of aggregates allows for asymmetric inheritance of damaged proteins, resulting in higher growth rates of damage‐free daughter cells. In contrast, symmetric damage inheritance of randomly distributed aggregates at the inner membrane abrogates this rejuvenation process, indicating that asymmetric deposition of protein aggregates is important for increasing the fitness of bacterial cell populations.
Gesehen am 26.02.2024